2012
DOI: 10.1152/ajpcell.00197.2011
|View full text |Cite
|
Sign up to set email alerts
|

Lithium reduces aquaporin-2 transcription independent of prostaglandins

Abstract: Vasopressin (AVP)-stimulated translocation and transcription of aquaporin-2 (AQP2) water channels in renal principal cells is essential for urine concentration. Twenty percent of patients treated with lithium develop nephrogenic diabetes insipidus (NDI), a disorder in which the kidney is unable to concentrate urine. In vivo and in mouse collecting duct (mpkCCD) cells, lithium treatment coincides with decreased AQP2 abundance and inactivation of glycogen synthase kinase (Gsk) 3β. This is paralleled in vivo by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 63 publications
3
38
0
Order By: Relevance
“…51,52 How the inhibition of GSK3 by lithium ultimately leads to NDI has not been identified but may involve b-catenin, which is increased in expression in lithiuminduced NDI and targeted for degradation by GSK3. 48,[53][54][55] Although basal b-catenin activity is necessary for AQP2 expression in collecting duct cell cultures, overactivation of the canonical Wnt-b-catenin pathway might contribute to lithiuminduced NDI, because it induces transcription of proliferative genes, which is also observed in principal cells of lithium-treated rodents. 56,57 Loss of polarization, which occurs with proliferation, reduces AQP2 expression in vitro.…”
Section: Toxic Effects Of Lithium Treatmentmentioning
confidence: 99%
“…51,52 How the inhibition of GSK3 by lithium ultimately leads to NDI has not been identified but may involve b-catenin, which is increased in expression in lithiuminduced NDI and targeted for degradation by GSK3. 48,[53][54][55] Although basal b-catenin activity is necessary for AQP2 expression in collecting duct cell cultures, overactivation of the canonical Wnt-b-catenin pathway might contribute to lithiuminduced NDI, because it induces transcription of proliferative genes, which is also observed in principal cells of lithium-treated rodents. 56,57 Loss of polarization, which occurs with proliferation, reduces AQP2 expression in vitro.…”
Section: Toxic Effects Of Lithium Treatmentmentioning
confidence: 99%
“…Previous studies have shown that pharmacological inhibition of GSK3 using LiCl, Zn, and 6-bromoindirubin-3=-oxime can reduce AQP2 levels in in vitro cell culture systems (20,21,24). However, these inhibitors are incapable of distinguishing between GSK3␣ and GSK3␤ isoforms.…”
Section: Gsk3␣ Is Expressed In Renal Collecting Ductsmentioning
confidence: 99%
“…NDI is the most frequently found undesirable effect of Li ϩ therapy, and it is found in up to 40% of patients (10,42). The primary cause of Li ϩ -induced NDI is the decrease in renal AQP2 expression (10), for which several mechanisms have been proposed, including altered AVP/cAMP and cyclooxygenase-2/PGE 2 signaling (4,21,23,24,37).…”
Section: Gsk3␣ Is An Important Regulator Of Renal Urine Concentrationmentioning
confidence: 99%
“…[9][10][11] Lithium also affects AQP2-mediated water reabsorption by the elevated tubular release of prostaglandin E 2 . [11][12][13] In a second phase, lithium reduces the percentage of principal cells in the collecting duct, which are "exchanged" for intercalated cells, involved in acid-base homeostasis. 14 Paradoxically, but in line with increased Wnt/b-catenin induced activity, 15,16 lithium is known to induce proliferation of principal cells.…”
mentioning
confidence: 99%